PERAMPINGAN (RIGHTSIZING) PADA PT. PERKEBUNAN NUSANTARA IX (PERSERO) DALAM WACANA KEBIJAKAN EFISIENSI MENJADI HOLDING COMPANY PT. PERKEBUNAN INDONESIA - , TALITHA LUTHFIA, Dr. Sulistiowati, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
State-Owned Enterprises generally possess in thirteen sectors with a total of more than 100 companies and The Ministry of State-Owned Enterprises continuously seek improvement both towards The Ministry itself and development of the enterprises. One of the main policy which is made to seek improvement of the enterprises is Restructuring Program. The Ministry of State-Owned Enterprises has been making a policy discourse to transform all of the plantation sector companies in to a holding company as listed in State-Owned Enterprises Rightsizing Program. Downsizing the scale towards a more ideal number of State-Owned Enterprises do for the benefit of the company itself and the national economy in general. A holding company form is chosen by State-Owned Enterprises which fulfilling the criteria such as same business sector, type of business and different market segments, high competition, but still have business prospects, and the government is the majority owner. PT. Perkebunan Nusantara IX (Persero) is one of the State-Owned Enterprises in plantation sector where the holding company policy discourse will be made.